Development Of Linear Displacement Sensor Using Meander Coil And Pattern Guide - Abdullah, Norrimah (2008)

(untitled)
In modern industrial production processes, the actual displacement of fast moving objects needs to be detected and it is ideally done without mechanical contact. There exists a variety of suitable sensors that provide an output signal (voltage or current) proportional to the displacement of the sensor target. The sensors must also meet the industrial requirements such as reliability, ruggedness and measuring range. To find the best sensor for the displacement purpose, accuracy, miniature size and insensitive to the environment factor is also very important to be considered. Magnetic sensor based on inductive concepts, has been widely used technique for measuring displacement. The most significant advantage of magnetic-inductive sensor in industrial applications is the immunity against oil, water, dirt, moisture and interference field. In addition, current development and trends in the industrial fields, especially micro-system and micro-mechanical applications like robotics and manipulator applications require utterly small and fully integrated displacement sensor.Linear motor is an example of linear actuator. The basic function of linear motor is for to generating a controlled physical linear displacement. Linear motor is essentially rotary electric motor laid down on flat surface. Linear motor, actuators converts an electrical signal (voltage or current) to mechanical displacement. This conversion is mostly used in robotics. Linear motor generally consists of two parts, a stationary track or “platen” and a moving part or “forcer”. In this study, displacement sensor based on the magneto-inductive concepts has been developed. It consists of sensor head and pattern guide. The structure of the sensor is based on the structure of the linear motor. The sensor head structure is based on the forcer and the pattern guide is based on the platen of the linear motor. In common systems, linear motor and the sensor have separate platen and forcer. Research focuses on integrating the sensor and the linear motor as a one body, in which the pattern guide of the sensor will be a platen and the sensor head will be a forcer of the linear motor. Therefore, the whole structure will be simple and thus reduce the overall cost and size. The combination of the sensor head and pattern guide is important to get the high accuracy of the positioning. The sensor head is made from the copper material while the pattern guide is made from soft iron SS400. Six configuration of the sensor head have been designed and fabricated based on their coil gap, Gm. To model the actual linear displacement sensor, the mathematical equation of the output voltage of the sensor has been derived. This equation describes the characteristic of the output voltage for linear displacement sensor based on the displacement of the pattern guide when certain input signal is applied to the sensor system. From the equation, the effect of input frequency on the output voltage of the sensor was analyzed and has been compared with the measurement data. The effect of the output voltage on the displacement of the pattern guide is observed for the open coil and the close coil condition. The results obtained have been analyzed in terms of sensitivity, hysteresis and linearity. The sensitivity of the sensor is calculated based on the highest changes of the output voltage for various input frequency, coil gap and exciting voltage. The output voltage for various input frequencies, exciting voltage and coil gap also have been compared in terms of hysteresis and linearity. The hysteresis of the output voltage for the sensor is based on the deviation of the sensor output at a specific point of input signal when it is approached from opposite direction. The linearity of the output voltage for the sensor is calculated using best-fit straight line (BPSL) method as being explained in the sensor characteristic in the Chapter 2.